Development and Evaluation of the Integrity of the Diniyah National Curriculum: Analysis of the Parallel Integration Model in Pesantren - Siti Sahra; Sabarudin Sabarudin; Muh Gaki Firman (LPPPM STAI Darul Hikmah Bangkalan, 2026)
This study analyzes the development of the integration of the national curriculum and the diniyah curriculum (Islam) and evaluates the quality of its implementation in the Pesantren Alkhairaat in Central Palu. Using a qualitative case study design, data was collected through field observation and in-depth interviews with 4 ustadz and 6 students who were selected purposively. Data analysis was carried out using the interactive model Miles, Huberman, and Saldana, including data condensation, presentation, and conclusion drawing and verification. The results of the study show that curriculum integration develops gradually and is currently implemented through a parallel model, with general learning in the morning and early learning in the afternoon to evening. The effectiveness of the implementation reached around 80%, despite facing limited facilities, tight schedules, and student adaptation to the two curriculum systems. Curriculum integration is still at the structural stage, but it has the potential to lead to substantial integration through strengthening integrative pedagogy, improving teacher competence, and facility support. These findings imply the need for cross-disciplinary teacher training, collaboration in integrated curriculum design, and investment in educational facilities. The research was limited to one case study; The next research is recommended to conduct a comparative study across pesantren to gain a more comprehensive understanding of the curriculum integration model in Indonesia